Discussing Global Citizenship through Collaborative Online International Learning (COIL) - Virtual Exchange (VE) in Language Learning and Teaching: Symposium Proceedings - Joanne Marsh, Michelle Mayer (Discussing Global Citizenship through Collaborative Online International Learning (COIL) - Virtual Exchange (VE) in Language Learning and Teaching: Symposium Proceedings, 2023)
This is the edited collection of the papers presented at an international symposium held at Coventry University in hybrid mode on 16th November 2022. The publication aims to share research findings and good Collaborative Online International Learning (COIL) - Virtual Exchange (VE) theory and practice for the development of global citizenship competences for the 21st Century, with a focus on language teacher education and language learning.The papers bring a variety of perspectives on COIL-VE for language learning and teaching and report on COIL-VE projects involving Higher Education Institutions from Spain, Brazil, France, Turkey, Vietnam and the UK.Each paper was peer-reviewed by three reviewers.